Anemia, diet, and cognitive development: Impact of health information on diet quality and child nutrition in rural India - Marion Krämer; Santosh Kumar; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2019)
Lack of information about health risks may limit adoption of improved nutritional and healthy behavior. This paper studies the effect of nutrition information intervention on household dietary behavior, child health, and cognitive ability of children in rural India. Using experimental data and regression discontinuity design that exploits the exogenous cutoff of hemoglobin level for anemia, we find statistically insignificant treatment effects on dietary improvements, child health, and cognitive outcomes of children. Our findings suggest that nutrition information alone, even when parents are informed about the anemia status of their children, may not promote healthy behavior and factors other than information might constrain households in making nutritional investments for their children.
Keywords: I12; I15; I18; O12; 330; Health information; Child health; Anemia; Cognition; Regression discontinuity; India